SWOT and Determinant Factors Approach to Worker Compliance Analysis with Full Body Harness Pass Systems in Construction Projects - Saraswati, R.A. Intan Dwi; Nugroho, Priyambodo Nur Ardi; Kurniasih, Dewi (Institut Teknologi Sepuluh Nopember, 2024)
Since construction sites are dangerous by nature, strict safety precautions are necessary. This study examines the Full Body Harness Pass system compliance of workers and the determinants that affect adherence with the aim of improving compliance and reducing avoidable accidents. A SWOT analysis methodology is utilized in the study to integrate quantitative compliance data with qualitative safety officer observations. Results show that though the FBH Pass system raises safety awareness, a number of issues, including poor training and reluctance to use digital tools, limit its utility. These recommendations go towards promoting an overall safer building environment, coupled with extended training programs and improved monitoring.